Heat penetration studies on bottled pickled cabbage (Brassica oleracea var. capitata L) for home scale thermal processing. - Autencio, Monette Alipio
With the growing concern of food loss and waste, particularly the increasing produce surplus in markets, reducing domestic food waste is vital as a step toward a more secure global food system. This study conducted heat penetration studies on bottled pickled cabbage for home scale thermal processing. The time-temperature history was gathered every 2 minutes using alcohol thermometers. The cold point in the canner during the water bath setup was located in the upper outermost region (6.67 cm distance from the top, 18 cm away from the center), whereas the cold point during the steam setup was situated in the lower central area of the canner (6.20 cm distance from the top, 9 cm away from the center). The geometric center was the slowest heating zone inside the glass jar. The effect of different process variables such as thermal medium, solid-to-liquid ratio, and bottle size on the heating characteristics of pickled cabbage was studied. Those jars packed with a 50:50 solid-to-liquid ratio, contained in small jars, and processed in a water bath achieved greater temperatures than the other experimental units. Three jars with the highest final temperatures were subjected to the Escherichia coli test. The results showed that experimental units that had undergone thermal processing achieved satisfactory levels of E. coli. This study shows the importance of temperature monitoring during thermal processing and how different variables affect the heating characteristics of a product. This study is also beneficial for small-scale processors to reduce losses and utilize produce surplus, specifically cabbage.